2021
DOI: 10.1101/2021.12.20.472748
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Oxytocin Signaling Regulates the Homeostatic Response to Cold Stress in Poikilothermic Vertebrates

Abstract: When exposed to low temperature, homeothermic vertebrates maintain internal body temperature by activating thermogenesis and by altered metabolism, synchronized by neuroendocrine responses. Although such physiological responses also occur in poikilothermic vertebrates, the prevailing notion is that their reactions are passive. Here, we explored molecular hypothalamic and physiological responses to cold stress in the tropical poikilotherm Nile tilapia (Oreochromis niloticus). We show that cold exposed tilapia e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 66 publications
(117 reference statements)
0
2
1
Order By: Relevance
“…7) . While cold stress has previously been shown to result in alternative splicing and changes in gene expression (36, 63, 64), our data indicates that it disproportionally affects the splicing of minor introns and expression of MIGs. The mechanism by which this specificity is achieved remains elusive and warrants further research.…”
Section: Discussioncontrasting
confidence: 52%
See 1 more Smart Citation
“…7) . While cold stress has previously been shown to result in alternative splicing and changes in gene expression (36, 63, 64), our data indicates that it disproportionally affects the splicing of minor introns and expression of MIGs. The mechanism by which this specificity is achieved remains elusive and warrants further research.…”
Section: Discussioncontrasting
confidence: 52%
“…Endotherms respond to environmental shifts in temperature by internally maintaining their core body temperature, while ectotherms such as fish and plants are susceptible to shifts in temperature. To test whether minor intron splicing is affected by environmental stresses such as cold exposure, we exposed the tropical poikilotherm Nile tilapia ( Oreochromis niloticus ) to acute cold stress by reducing the water temperature from 25°C to 14°C, at a rate of −1°C/h (36). RNAseq of the hypothalamus, a crucial thermoregulation center in the brain, revealed that over 20% of all minor introns were mis-spliced upon cold exposure, while only a small number of minor-like, hybrid and major-like introns were affected (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Although capacity is reduced at low temperatures, the integrity of the Mozambique tilapia PepT2 activity is maintained. It had been shown that tilapia actively lowering their metabolism levels in response to cold challenges ( Segev-Hadar et al, 2021 ). Our results indicate that peptide transport at low temperature is feasible and can continuously supply nutrients to support metabolic function.…”
Section: Discussionmentioning
confidence: 99%